Kontroversi Regulasi Penyiaran di Indonesia - Mr Masduki (Jurnal Komunikasi, 2006)
Conflict and controversy on broadcast regulation in Indonesia, come from the collaboration of various thoughts and interests in the process of law decision. Result of qualitative analysis on Broadcasting Law no. 32/2002 and some lower government policies indicates that, there were economic and political thoughts influencing the Law. The three thoughts were authoritarianism, neo-liberalism and democracy. Authoritarianism existed in rule that, government remain hold broadcast frequency licensing such as in The New Order era. Neo liberalism was included in regulation to allowing foreign capital and human resources entering broadcast industry and proposal to private RRI (Indonesian Republic Radio) and TVRI (Indonesian Republic Television). Democratization existed in rule to place an Independent regulatory body, to replace government position. Both ideas, to revise Law no. 32/2002 and government neutral position in this process are the alternative solutions to minimize conflict among stakeholders.